Transparency Watchdog: Guarding the Law and Independent from Politics? The Relationship between the European Ombudsman and the European Parliament - Neuhold, Christine (2017)
This article investigates whether the European Ombudsman acts as an ‘independent’ institution vis-à-vis the European Parliament (EP). This is a relevant question because while the Ombudsman is appointed by and reports to the EP, it can also conduct inquiries into the work of the EP, in instances of alleged maladministration. Based on the empirical examination of all decisions following an inquiry by the Ombudsman in cases against the EP for an eleven-year period (2004–2015), plus the review of two recent landmark own-initiative inquiries, we inductively construct three roles played by the Ombudsman in relation to the EP, namely: ‘arbitrator’, ‘transparency watchdog’, and ‘vessel for civil society concerns’. These roles are used to operationalize the concept of independence. We conclude that the Ombudsman acts independently and is not a mere auxiliary organ of the European legislature. This is most apparent in the ‘transparency watchdog’ role, where the European Ombudsman has ensured the release of information empowering citizens to hold the Parliament accountable, or—failing that—has stimulated debate concerning such information (for instance, on the MEPs’ financial allowances) both within the Parliament itself and in the wider public domain.